2016
DOI: 10.1111/tbed.12500
|View full text |Cite
|
Sign up to set email alerts
|

Hydropericardium Hepatitis Syndrome Emerged in Cherry Valley Ducks in China

Abstract: Since June 2015, a highly pathogenic disease occurred in duck flocks in China, causing pericardial effusion, enlarged discoloured liver, renal enlargement and haemorrhagic lung with a mortality ranging from 5% to 20%. Previous study confirmed that Fowl adenovirus group C (FAdV-C) and some field FAdVs isolates had been identified as causative agents of hydropericardium hepatitis syndrome (HHS) in chickens and geese world widely. In this study, we firstly report the isolation of FAdV-C from ducks with HHS. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…These results are consistent with those found in a previous study ( 39 ). However, in Chen’s study, the duck source FAdV-4-infected ducks showed typical hydropericardium and death with the intracerebral infection route used ( 28 ). Why does the same viral cause such different reactions in chickens and ducks?…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results are consistent with those found in a previous study ( 39 ). However, in Chen’s study, the duck source FAdV-4-infected ducks showed typical hydropericardium and death with the intracerebral infection route used ( 28 ). Why does the same viral cause such different reactions in chickens and ducks?…”
Section: Discussionmentioning
confidence: 98%
“…Combined with the acute and fatal events caused by FAdV-4 in chickens, it is interesting to learn whether ducks have the same or similar symptoms after FAdV-4 infection. Chen’s study suggests that FAdV-4 also causes hydropericardium in ducks, resulting in death after intracerebral injection ( 28 ). We comparatively studied the differences in pathogenicity between SPF chickens and SPF ducks and examined the various antiviral innate immune responses in these two fowl.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, outbreaks of HHS in many chicken farms in China resulted in significant economic losses and the causative agent was identified as FAdV-4 by DNA sequencing, phylogenetic analysis and virus isolation (Li et al, 2016;Niu et al, 2016). Occurrence of HHS in ducks was also reported in China, and hexon gene sequencing together with phylogenetic analysis revealed the aetiologic agent was FAdV-4 (Chen et al, 2016). To date, a simple and specific method for rapid detection and differentiation of FAdV-4 is still unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…According to the genome sequence analysis, this epidemic FAdV-4 is a novel genotype (Ye et al, 2016). Furthermore, hydropericardium hepatitis syndrome has been reported to be emerging in Cherry Valley ducks in China, and the disease is also induced by FAdV-4 (Chen et al, 2016). However, no complete genome sequence of FAdV-4 isolated from ducks has been available, which is very important for understanding the evolution and cross-transmission between different hosts.…”
Section: Discussionmentioning
confidence: 99%
“…FAdVs are common infectious agents in poultry, although most of them have been isolated from chickens (Eregae et al, 2014;Mittal et al, 2014;Rahimi & Minoosh, 2015); therefore, most complete genome sequences of FAdVs are of strains isolated from chickens with or without significant clinical signs (Sheppard et al, 1995;Vera-Hernández et al, 2015;Li et al, 2016). However, very recently, hydropericardium hepatitis syndrome associated with FAdV-4 infection emerged in ducks in China (Chen et al, 2016). Several complete genome sequences of hypervirulent FAdVs isolated from chickens have been submitted to GenBank and show some characteristics of new genotypes (Ye et al, 2016), but no complete genome sequence of fowl adenovirus isolated from ducks was available until now.…”
Section: Introductionmentioning
confidence: 99%